Investigating Efl Teachers’ Perceptions In Vocational High Schools Toward English For Specific Purpose (Esp) Classroom - Muhammad Guntar (SNHRP, 2023)
The objective of teaching ESP is to make students to be able to use English that is suitable in their major context. Teachers’ perception in the classrooms is crucial in teaching – learning process. They can identify various points of view and gain a better understanding of who their students truly are. The aim of the present study is to investigate teachers’ perceptions in vocational high schools toward ESP. In this study, researchers utilized descriptive qualitative method. The participants of the study were 10 EFL teachers in vocational schools. The method of data collection was done through questionnaire using Likert-scale. The findings of the study highlighted the focuses that were considered crucial by the teachers to the teaching of ESP, namely focus on learning, discipline, needs, skills and strategies, and also focus on language. Further, ESP teachers may need to put more emphasis on students' competency development. Also, the findings of this study suggest that as part of their ongoing professional development, teachers should be made aware of the requirements of their students in relation to their course curriculum, in addition to their own material expertise and teaching strategies. As a result, the students are able to relate to the ESP teaching purpose.